ANALISIS PENGELOLAAN LIMBAH B3 MEDIS PASCA VAKSINASI COVID-19 DI PUSKESMAS KABIL TAHUN 2022 - Winda Wikansari; Al Hafez Husein; M Kafit (Jurnal Kesehatan Ibnu Sina (j-kis), 2023)
The Covid-19 pandemic has an impact on increasing Covid-19 vaccination activities, resulting in an increase in the amount of medical waste. One of them is at the Kabil Health Center, Batam City. The study was conducted to analyze the management of solid medical B3 waste after the covid-19 vaccination at the Kabil Health Center, Batam City in 2022. This research method was carried out qualitatively with an analytical approach with in-depth interviews, field observations, and document review, based on purposive sampling. The data were analyzed by means of data reduction, data presentation, and drawing conclusions. Data is presented in tabular form. The results of the research analysis are that there are no human resources who have attended training on B3 waste management, no routine medical check-ups have been carried out, and there is no special immunization for B3 waste managers. The lack of budget is also a problem for the unavailability of transportation equipment in the form of trolleys and also TPS that have storage permits. In addition, storage is carried out for more than 2 (two) days since the solid medical B3 waste after the covid-19 vaccination is produced. Irregular transport schedules also cause B3 waste to accumulate in storage warehouses. Conclusion The management of solid medical B3 waste after the covid-19 vaccination at the Kabil Health Center, Batam City is still not in accordance with PermenLHK No. 56 of 2015, and SE No. 3 of 2021. Suggestions are expected for the puskesmas to improve monitoring and evaluation efforts on the implementation of the SOP regarding the management of B3 waste after the covid-19 vaccination.